1991
DOI: 10.1002/ajmg.1320380403
|View full text |Cite
|
Sign up to set email alerts
|

Duplication 3q(q21 → qter) without limb anomalies

Abstract: We report on a 2.5-month-old boy with hypertelorism, hypertrichosis, anteverted nostrils, malformed ears, thin lips, downturned corners of the mouth, micrognathia, short neck, cryptorchidism, and bilateral simian creases without limb anomalies. Cytogenetic studies showed a duplication 3q----qter 46,XY,der(6),t(3;6)(q21;p25)pat. The absence of limb anomalies is noteworthy; all 12 previously reported patients with the same duplication had limb anomalies. The uniqueness of this report provokes speculations regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Also, a female with a dup3q27‐qter presented without any gastrointestinal, renal or cardiac anomalies , indicating that these features might be attributable to the duplicated proximal region. On the other hand, Ismail et al reported a duplication of 3q21‐qter in a boy without any limb anomalies.…”
Section: Phenotypic Features Of Patients With ‘Pure’ Duplication 3qmentioning
confidence: 99%
“…Also, a female with a dup3q27‐qter presented without any gastrointestinal, renal or cardiac anomalies , indicating that these features might be attributable to the duplicated proximal region. On the other hand, Ismail et al reported a duplication of 3q21‐qter in a boy without any limb anomalies.…”
Section: Phenotypic Features Of Patients With ‘Pure’ Duplication 3qmentioning
confidence: 99%
“…Reciprocal translocation is the most frequent parental chromosome anomaly. In our case, parental chromosome analysis demonstrated a maternal pericentric inversion of chromosome 3 (46, XX, inv (3) (p26q21) • Renal anomalies (Blumberg, 1980) • Renal cystic dysplasia (Blumberg, 1980) • Renal cortical cysts (Chiyo, 1976;Fear, 1979) • Unilateral renal agenesis (Blumberg, 1980) • Renal calcification (Ismail, 1991) • Adrenal neuroblastoma (Qureshi, 1994) • Malrotation (Blumberg, 1980) • Lung hypoplasia (Blumberg, 1980;Qureshi, 1994) • Omphalocele (Mulcahy, 1979;Chen, 1996;Yatsenko, 2003;Park, 2008) Central nervous • Dandy-Walker malformation (Chiyo, 1976; de Azevedo Moreira, 2005) Ventriculomegaly system • Cerebellar hypoplasia (Steinbach, 1979) • Arhinencephaly (Steinbach, 1979) • Hypoplasia of corpus callosum (Steinbach, 1979) • Microcephally (Blumberg, 1980) • Spina bifida (de Azevedo Moreira, 2005; Gimelli, 2007) Genital system • Hypospadias (Fryns, 1984) • Bicornuate uterus (Chiyo, 1979;Blumberg, 1980) • Streak ovaries (Blumberg, 1980) • Duplication of the vagina and cervix (Blumberg, 1980) • Ambiguous genitalia (Gimelli, 2007) Anal anomalies • Anteriorly placed anus (Fryns, 1979) • Anal stenosis (Gustashaw, 1985) …”
Section: Discussionmentioning
confidence: 49%
“…• Congenital glaucoma (Kondo,1979;Blumberg, 1980) • Coloboma of optic nerve (Ayral, 1984) • Hypertelorism (Ismail, 1991 • Narrow pelvis (Steinbach, 1981) • Dislocated elbow (Steinbach, 1981; Zafra de la Rosa, 2005)…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, heart defects are also common (Faas et al, 2002;Ounap et al, 2005;Steiner et al, 2011;Rodríguez et al, 2014;Zhu et al, 2013). Other anomalies, including genitourinary and skeletal abnormalities, are also reported (Wilson et al, 1985;Preus et al, 1986;Ismail et al, 1991;van Essen et al, 1991;Lopez-Rangel et al, 1993;Aqua et al, 1995;Chen et al, 1996;Rizzu et al, 1997;Kroisel et al, 2000).…”
Section: Introductionmentioning
confidence: 85%
“…Partial duplication of chromosome 3q is known to cause a malformation syndrome in most patients presenting with an unbalanced translocation with other chromosomes or inversions of chromosome 3q (Wilson et al, 1985;Preus et al, 1986;Ismail et al, 1991;van Essen et al, 1991;Lopez-Rangel et al, 1993;Aqua et al, 1995;Chen et al, 1996;Rizzu et al, 1997;Kroisel et al, 2000;Faas et al, 2002, Ounap et al, 2005. Phenotypic manifestations include characteristic facial anomalies such as synophrys, broad nasal root, anteverted nares, downturned corners of the mouth with long philtrum, microretrognathia, low-set ears, generalized hypertrichosis as well as hand and feet anomalies and different degrees of intellectual disability.…”
Section: Introductionmentioning
confidence: 97%